PELAKSANAAN PEMBEBASAN BERSYARAT TERHADAP WARGA BINAAN DI LEMBAGA PEMASYARAKATAN KELAS IIA BUKITTINGGI (Studi Narapidana Narkotika) - M. Al Faddri Fajar; Lola Yustrisia; Syaiful Munandar (Ensiklopedia of Journal, 2023)
Human life is a gift from God Almighty that must be lived by every human being based on the usual rules of life. The State of Indonesia has several types of law, including Criminal Law and Criminal Procedure Code. In relation to the purpose of punishment in Indonesia, Law Number 22 of 2022 concerning Corrections is elaborated. Where an inmate who is serving his sentence in a Correctional Institution has rights, as stated in Article 10 paragraph (1) one of the rights obtained by a convict is to get parole. This is the urgency of the research, namely the researcher wants to examine the implementation of parole, the obstacles and efforts to overcome them. The method used in this research is Empirical Law with the research specification is descriptive and the data collection technique uses literature study with qualitative data analysis methods. The results of the research on the formulation of the problem are the implementation of parole and the coaching program for inmates, and the constraints faced by correctional officers both internally and externally. And what has been regulated in the applicable laws and regulations regarding Corrections.